Evaluation of geochemical reactivity of hydrogen in sandstone: Application to geological storage. (August 2018) - Yekta, Alireza E.; Pichavant, Michel; Audigane, Pascal
Abstract: The use of hydrogen as an alternative for electric energy storage has emerged recently. Being composed of small molecules, hydrogen has a strong ability to migrate in porous medium and can also be highly reactive with rock-forming minerals. In the case of storage in sedimentary rocks such as sandstone, mineralogical transformations due to the presence of hydrogen may modify the porous structure of the rock and affect the storage properties. In this study, the geochemical reactivity of hydrogen with sandstone was assessed both experimentally and numerically. Experiments were performed to test the possibility of mineral transformations due to hydrogen, either pure or in presence of water. The experiments were carried out mostly at 100 and more rarely at 200 °C. Maximum hydrogen pressures of 100 bar were imposed and experimental durations ranged from 1.5 to 6 months. The experimental products bear the mark of only very limited reaction between minerals in sandstone and hydrogen. Taken together with the numerical results, this study demonstrates that hydrogen, once injected, can be considered as relatively inert. Overall, our results support the feasibility of hydrogen confinement in geological reservoirs such as sandstones. Highlights: The interaction of hydrogen with rock minerals were studied. Minor modifications of sandstone mineralogy identified in experimental results because of the presence of hydrogen. The experimental results indicate that mineral reactions take place in sandstone during interaction with hydrogen. Numerical results indicate little effect on the dissolution of minerals except hematite due to presence of hydrogen. Microstructure and rock physical properties are unmodified.